1999
DOI: 10.1136/thx.54.8.664
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between early life respiratory illness, family size over time, and the development of asthma and hay fever: a seven year follow up study

Abstract: Background-The timing and mechanism of the inverse association between increasing sibling number and atopic disease are not yet understood. A study was undertaken to examine how family size at birth predicts early respiratory illness, to report the association between infant respiratory illness and childhood atopic disease, and to determine whether the protective eVect of large family size operates during infancy or later childhood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
76
3
7

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(92 citation statements)
references
References 31 publications
6
76
3
7
Order By: Relevance
“…[22][23][24][25][26][27][28] Several epidemiologic findings support the hygiene hypothesis. [22][23][24][25][26][27][28] For example, children are less likely to have allergies if they are part of a large family, attend child care, experience a large number of infections early in childhood, or come in contact with animals. On the other hand, children are more likely to have allergies if they live in areas of better sanitation, are not infected with helminths or worms, or live a "Western" lifestyle.…”
Section: Mechanisms Proposed To Explain How Vaccines Might Cause Allementioning
confidence: 54%
“…[22][23][24][25][26][27][28] Several epidemiologic findings support the hygiene hypothesis. [22][23][24][25][26][27][28] For example, children are less likely to have allergies if they are part of a large family, attend child care, experience a large number of infections early in childhood, or come in contact with animals. On the other hand, children are more likely to have allergies if they live in areas of better sanitation, are not infected with helminths or worms, or live a "Western" lifestyle.…”
Section: Mechanisms Proposed To Explain How Vaccines Might Cause Allementioning
confidence: 54%
“…[11][12][13] A common interpretation of these results has been that older siblings and child care attendance are indirect measures of earlylife infections and that early-life infections have a preventive effect on the development of atopic disorders. A number of studies have also assessed the relation between atopic disorders and direct measures of early-life infections, 11,[13][14][15][16][17][18][19][20][21][22][23] but fewer have been able to do this prospectively. [13][14][15][18][19][20][21][22] Studies that have used direct measures of infections have shown less consistent results than the studies that have used indirect measures, and the inverse relation has often been restricted to subgroups of diseased individuals, mainly those with atopic predisposition.…”
mentioning
confidence: 99%
“…A number of studies have also assessed the relation between atopic disorders and direct measures of early-life infections, 11,13-23 but fewer have been able to do this prospectively. [13][14][15][18][19][20][21][22] Studies that have used direct measures of infections have shown less consistent results than the studies that have used indirect measures, and the inverse relation has often been restricted to subgroups of diseased individuals, mainly those with atopic predisposition. Furthermore, childhood asthma has been found to be more common in children who experienced at least 1 specific type of early respiratory infection, namely respiratory syncytial virus infection.…”
mentioning
confidence: 99%
“…However, previous studies consistently reported a significant relationship between number of siblings and allergic rhinitis, independent of day-care attendance and history of infections. 20,21 Our study shows that the larger number of siblings is associated with the lower incidence of allergic rhinitis, and non-first-born birth order is associated with lower incidence of allergic rhinitis. Further study with a larger sample size is needed to evaluate the relationship of number of siblings on the incidence of allergic rhinitis and to adjust for other risk factors that may affect the incidence of allergic rhinitis in children.…”
Section: Discussionmentioning
confidence: 86%